Cotton-Tipped Plastic Swabs for SARS-CoV-2 RT-qPCR Diagnosis to Prevent Supply Shortages - Freire-Paspuel, Byron; Vega-Mariño, Patricio; Velez, Alberto; Castillo, Paulina; Gomez-Santos, Eliana Elizabeth; Cruz, Marilyn; Garcia-Bereguiain, Miguel Angel (Frontiers in Cellular and Infection Microbiology, 2020)
CDC and WHO guidelines for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) diagnosis only recommend synthetic fiber swabs for nasopharyngeal (NP) sampling. We show that cotton-tipped plastic swabs do not inhibit PCR and have equivalent performance to rayon swabs. Cotton-tipped plastic swabs are massively produced worldwide and would prevent swab supply shortages under the current high SARS-CoV-2 testing demands, particularly in developing countries.